Directly and Indirectly Acting Photoinitiating Systems for Ring‐Opening Polymerization of ϵ‐Caprolactone - Bener, Semira; Yilmaz, Gorkem; Yagci, Yusuf (Wiley, 2021)
AbstractDirectly and indirectly acting photoinitiating systems for cationic ring opening polymerization (ROP) of ϵ‐caprolactone (ϵ‐CL) by using diphenyl iodonium salt (DPI) in the presence of benzyl alcohol were studied and mechanistic details were evaluated. In the direct system, the polymerization is initiated by a Brønsted acid formed upon UV irradiation of DPI. Polymerizations by indirectly acting photoinitiating systems proceeding via electron transfer reactions of photochemically formed electron donor radicals or excited states of polynuclear aromatic compounds with DPI were investigated. It was demonstrated that polymerizations proceed in a controlled manner by an activated monomer (AM) mechanism. Applicability of the photoinitiation to the other lactone monomers was validated on the example of δ‐ valerolactone (δ‐VL).